Vitamin K deficiency bleeding after NICE guidance and withdrawal of Konakion Neonatal: British Paediatric Surveillance Unit study, 2006–2008. Issue 1 (12th November 2012) - Busfield, Alison; Samuel, Rebecca; McNinch, Andrew; Tripp, John H
Abstract : Objective: To survey vitamin K deficiency bleeding (VKDB) and document vitamin K (VK) prophylaxis practice, and compare with findings predating withdrawal of Konakion Neonatal and guidance from the National Institute of Health and Clinical Excellence (NICE), both occurring in 2006. Design: Two-year surveillance of VKDB (2006–2008) using British Paediatric Surveillance Unit methodology. Postal questionnaire to consultant-led maternity units. Setting: UK and Irish Republic. Patients: All newborns and infants under 6 months with suspected VKDB. Main outcome measures: VKDB incidence and predisposing factors, VK prophylaxis recommended/received. Results: Eleven cases of VKDB were found: six (55%) babies received no VK prophylaxis, in five (45.5%) because parents withheld consent; three (27.5%) babies with late VKDB received intramuscular (IM) Konakion MM (two had biliary atresia, and one was delivered preterm); two (18%) babies received incomplete oral prophylaxis. Nine babies (82%) were breast fed. Three (27%) babies had liver disease; four (36%), including all those with liver disease, were jaundiced at presentation after 21 days. Four (36%) babies had intracranial haemorrhage, two probably suffering long-term morbidity. VK prophylaxis practice was defined in 236 (100%) units. All units recommended prophylaxis for every newborn: 169 (72%) IM, 19 (8%) oral, and 48 (20%) offered parental choice. All units that recommended IM prophylaxis used Konakion MM. Oral prophylaxis always involved multidose regimens for breastfed babies; 61 (91%) units used Konakion MM, and six (9%) used unlicensed products suitable for administration by parents. Conclusions: IM Konakion MM is efficacious, but parents withholding consent for recommended IM prophylaxis reduces effectiveness. Reappraisal of NICE guidance would be appropriate. Prolonged jaundice demands investigation. Late VKDB occasionally occurs after IM prophylaxis.